2021
DOI: 10.1177/02676591211046876
|View full text |Cite
|
Sign up to set email alerts
|

An infant with suspected missed diagnosis of Williams syndrome failed weaning off CPB after surgical correction of pulmonary stenosis: a case report and literature review

Abstract: Williams syndrome (WS) is a rare congenital developmental disorder caused by the deletion of between 26 and 28 genes on chromosome 7q11.23. For patients with WS, in view of the particularity of the supravalvular aortic stenosis, choosing appropriate arterial cannula, maintaining higher perfusion pressure as well as strengthening myocardial protection during cardiopulmonary bypass (CPB) is essential to the clinical outcome. Here, we report a child with pulmonary artery valvular stenosis who failed to wean off C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The patient had poor cardiac function, and electrocardiogram indicated myocardial ischemia. Although the combination of high end-diastolic pressure due to severe SVAS coupled with coronary artery stenosis can result in decreased coronary artery perfusion pressure and myocardial ischemia ( 12 ), ultimately resulting in cardiac dysfunction and papillary muscle and endocardial calcification, it often takes a long time to develop. In the present study, echocardiography showed no significant coronary artery stenosis, so the decrease in cardiac function and endocardial calcification could not be explained by SVAS alone.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had poor cardiac function, and electrocardiogram indicated myocardial ischemia. Although the combination of high end-diastolic pressure due to severe SVAS coupled with coronary artery stenosis can result in decreased coronary artery perfusion pressure and myocardial ischemia ( 12 ), ultimately resulting in cardiac dysfunction and papillary muscle and endocardial calcification, it often takes a long time to develop. In the present study, echocardiography showed no significant coronary artery stenosis, so the decrease in cardiac function and endocardial calcification could not be explained by SVAS alone.…”
Section: Discussionmentioning
confidence: 99%